Oxytocin or Social Housing Alleviates Local Burn Injury in Rats - YEGEN, BERRAK; ERZİK, CAN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2010)
Background. Thermal injury may cause distant organ inflammation and multiorgan failure. Oxytocin (OT), a nonapeptide, modulates the immune and inflammatory processes. Materials and Methods. To investigate the effects of oxytocin on burn-induced tissue injury, Sprague-Dawley rats were subjected to a partial thickness burn. Immediately after burn, half of the burned rats were placed single in the cages, while others were caged in groups. All the rats then were treated with either OT (5 mu g/kg, s.c) or saline twice daily for 5 d. The control rats had no burn injury and received no treatments. On day 5, the rats were decapitated, tissue and serum samples were obtained to score the severity of damage and to assay TNF-alpha levels. Results. Burn trauma resulted in oxidative ileal damage, as evidenced by increased apoptotic rate, increased neutrophil recruitment, and enhanced lipid peroxidation. OT treatment depressed the TNF-a level and alleviated dermal degeneration, while attenuating ileal damage. Although a higher degree of skin damage was observed in the animals kept isolated following burn injury, keeping the rats in groups did not affect the level of TNF-a or the severity of dermal or ileal injury, but abolished the burn-induced elevations in ileal lipid peroxidation and myeloperoxidase activity. Moreover, OT treatment reduced the ileal apoptosis when applied to rats housed in groups, while the treatment did not alter apoptotic ratio in the isolated rats. Conclusion. Oxytocin can be considered as a potential agent in treating burn-induced distant organ injury. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: oxytocin; burn; oxidative damage; social interactions; TNF-alpha; ATRIAL-NATRIURETIC-PEPTIDE; MULTIPLE ORGAN FAILURE; RECEPTOR MESSENGER-RNA; GASTROINTESTINAL-TRACT; THERMAL-INJURY; IN-VITRO; DAMAGE; INFLAMMATION; VASOPRESSIN; INTERLEUKIN-6